دراسة اقتصادية لإنتاج واستهلاك الأسماك في مصر - الطوخي، مصطفى الشحات; خطاب، منال محمد سامي (الجمعية المصرية للإقتصاد الزراعي, 2020)
بالرغم من تمتع مصر بمساحات واسعة من المسطحات المائية إلا أن إنتاجها من الأسماك لا يكفي احتياجاتها الاستهلاكية لذا فقد استهدف هذا البحث التعرف على الوضع الراهن لإنتاج واستهلاك الأسماك في مصر، حيث مثل الإنتاج من الاستزراع السمكي نحو ۷۳% من إجمالي كمية إنتاج الأسماك في مصر، وجاءت أسماك البلطي كأهم الأصناف السمكية المنتجة بمتوسط بلغ نحو ٦١%، واحتلت محافظة كفر الشيخ المرتبة الأولى كأكبر المحافظات المنتجة بمتوسط بلغ نحو ٤٣% من إجمالي كمية إنتاج الأسماك في مصر، وقد زادت كميات الإنتاج الشهرية بالمصايد الطبيعية خلال الشهور من سبتمبر إلى ديسمبر بينما انخفضت في بقية الشهور عن المتوسط الشهري العام لها، وأن كلا من كمية الإنتاج المحلي من الأسماك، وكمية الواردات المصرية منها هما أهم العوامل المؤثرة على متوسط استهلاك الفرد من الأسماك. Although Egypt has large areas of water, its production of fish is not sufficient for its consumption needs. This research aimed to study the current situation of fish production and consumption in Egypt. The most important research findings were as follows: - The relative importance of production from natural sources, the total amount of fish production from marine water, the relative importance of it, the amount of freshwater production, the relative importance of it, the relative importance of production from lakes have decreased during the period (2005-2018) at rates that reached respectively, about 6.4%, 1.47%, 7.48%, 2.46%, 8.86%, 4.52% of the annual average for each, while the total production and production from fish farming, the relative importance of it, and the total amount of fish production from the lakes took an increasing general trend with an annual increase rates reached, respectively, about 5.6%, 7.9%, 2.3%, 1.39% of the average Annual for each. - The average amount of production from both the private farms and the floating cages combined together represented about 96.4% of the total production of fish farming, and about 70.5% of the average amount of total fish production in Egypt during the study period, and it was found that the quantities of fish production from Private farms, floating cages, and government farms have taken an increasing general trend during the study period, with rates respectively amounting to 7.89%, 8.95%, 7.7% of the annual average for each. - Tilapia fish ranked first as the largest fish species produced in Egypt during the period (2014-2018) with an average represented about 61% of the total fish production, followed by mullet, and carp, which respectively represented about 12.4%, 10.8% of the total fish production. The total production of these three varieties combined represented about 84.2% of the average of the total fish production in Egypt during the study period. Kafr El-Sheikh Governorate ranked first as the largest fish-producing governorate in Egypt during the period (2014-2018) with an average represented about 43.2%, followed by Port Said, Damietta, Sharkia and Beheira, governorates, the average production of each of them, respectively, represented about 14.1%, 10.3%, 8.6%, 6.5% of the average of the total fish production in Egypt, and the total production from these five governorates combined represented about 82.7% of the average of the total fish production in Egypt during the study period. - The monthly production quantities during the months of September to December have exceeded the average monthly production amount during the study period, respectively, by 8.2%, 22.8%, 14.7% and 7.1%, while the monthly production quantities during the months from January to August are less than the average monthly production quantity during the study period, respectively, about 5.3%, 8.6%, 3.8%, 6.5%, 6.4%, 9.8%, 9.3% and 3%.
The quantities available for consumption, the fish gap and the average per capita consumption of fish in Egypt increased during the period (2005-2018) at annual rates, respectively, represented about 5.82%, 6.64%, 3.4% of the annual average for each. -The increase in the amount of total production of fish in Egypt, the amount of Egyptian imports of fish, the retail prices of both meat and poultry, the food gap from both meat and poultry, and the average per capita national income by 10% leads to an increase in the average per capita consumption of them, respectively, by about 5.8%, 3.1%, 2.5%, 3.1%, 1.8%, 1.4%, 2% while increasing the relative price between tilapia and meat by 10% reduces the average per capita fish consumption by 7.8%, as it was found that about 98% of the changes in the average Per capita fish consumption during the period (2005-2018) is due to the change in the total domestic production of fish and the amount of Egyptian imports of fish.
Keywords: الإنتاج السمكي -- أصناف الأسماك -- المياه البحرية -- الفجوة الغذائية -- مصر